Postural stability analysis of center of pressure data from normal and flat feet during upright standing using signal energy - Tsui-Chiao Chao (International Journal of Management, Economics and Social Sciences (IJMESS), 2017)
This study applied the signal energy (SE) method using center of pressure (COP) data to quantify postural stability. A randomized control trial was conducted to determine differences between subjects with normal and flat feet. Fifty-four subjects aged 18- 30 years participated; 37 normal and 17 flat foot subjects. All subjects undertook tasks commonly used to quantify postural stability. Measurements quantified using the SE method were compared with those quantified using commonly employed methods for assessing postural stability. Using the SE method, total energy values required for maintaining postural stability with flat feet differed significantly (p < 0.05) compared with normal feet when eyes were open and closed in the medial-lateral direction. Signal amplification and observed variance were demonstrated by the SE method, and can be used to clarify differences in quantitative postural stability between normal and flat feet. Hence, SE might be a valid biometric method for balance control assessment; however, further study of subjects from different age groups is required to validate the application of the SE method in postural stability quantification.
Keywords: 330; Flatfoot; postural stability; signal energy; information systems; physical sciences and engineering